Body, sexuality, marriage and feminism: an interview with Jane Gallop. Issue 8 (17th November 2021) - Karmakar, Goutam
ABSTRACT: This conversation draws on the connection between feminist and psychoanalytic theory and how Freudian psychoanalytic theory has inspired feminists to perceive sexuality 'beyond biology'. It specifically focuses on Jane Gallop's ideas on sexuality, seduction, feminism, marriage, patriarchy, language, disability and academia through some of her key writings: The Daughter's Seduction: Feminism and Psychoanalysis (1982), Thinking Through the Body (1987), Around 1981: Academic Feminist Literary Theory (1992), Feminist Accused of Sexual Harassment (1997) and Sexuality, Disability, and Ageing: Queer Temporalities of the Phallus (2019). The challenge Gallop presents to conventional ideas of sexuality and body are explored.